A glitch in the matrix: organ-specific matrisomes in metastatic niches. Issue 2 (February 2022) - Deasy, Sarah K.; Erez, Neta
Abstract : Modification of the extracellular matrix (ECM) is a critical aspect of developing a metastasis-supportive organ niche. Recent work investigating ECM changes that facilitate metastasis has revealed ways in which different metastatic organ niches are similar as well as the distinct characteristics that make them unique. In this review, we present recent findings regarding how ECM modifications support metastasis in four frequent metastatic sites: the lung, liver, bone, and brain. We discuss ways in which these modifications are shared between metastatic organs as well as features specific to each location. We also discuss areas of technical innovation that could be advantageous to future research and areas of inquiry that merit further investigation. Highlights: The extracellular matrix (ECM) of different organs are composed of distinct combinations of matrisomal proteins; metastasis-supportive modifications of these ECMs can be similarly specific to each organ niche while sharing commonalities. Tumor-derived extracellular vesicles (EVs) home to lung fibroblasts, activate them to cancer-associated fibroblasts (CAFs), and induce a metastasis-supportive microenvironment through collagen and fibronectin deposition and ECM modification. Immune cells play a significant role in profibrotic changes in the liver and lung metastatic niches. The bone and brain have unique ECM compositions that produce singular types of modifications. Increased understanding of metastasis-supportive ECM changes has enabled development of more accurate models and revealed important clinical considerations. Novel therapeutic approaches for targeting of ECM changes in the premetastatic niche may be beneficial in preventing metastatic relapse.